2003
DOI: 10.1249/01.mss.0000089339.07610.5f
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of Muscle Function after 21-Day Forearm Immobilization

Abstract: In this model, 21-d forearm immobilization caused no significant changes in forearm muscle morphology, but the muscle function showed remarkable deterioration ranging from 18 to 45%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 20 publications
4
69
1
Order By: Relevance
“…However, if we take the decreased O 2 ,fast to mean a more facilitated recruitment of type II fibers or a delayed response in O 2 , this would indicate that the energy-supplying system becomes dependent on glycolysis more than oxidation and that more lactate is produced. This possibility is supported by reports demonstrating that muscle oxidative capacity decreases after inactivity [7,24]. Therefore after ULLS, the subjects might be harder pressed to carry out the exercise tasks.…”
Section: What the Declined Asymptote In The Fast Component Of O 2 Impmentioning
confidence: 54%
See 2 more Smart Citations
“…However, if we take the decreased O 2 ,fast to mean a more facilitated recruitment of type II fibers or a delayed response in O 2 , this would indicate that the energy-supplying system becomes dependent on glycolysis more than oxidation and that more lactate is produced. This possibility is supported by reports demonstrating that muscle oxidative capacity decreases after inactivity [7,24]. Therefore after ULLS, the subjects might be harder pressed to carry out the exercise tasks.…”
Section: What the Declined Asymptote In The Fast Component Of O 2 Impmentioning
confidence: 54%
“…Previous studies have demonstrated that limb disuse by casting attenuated the muscle oxidative capacity in the immobilized limb [7], that ULLS reduced the femoral artery diameter in the side of the suspended leg [9], and that the number and luminal diameter of capillaries in the muscles of rats decreased after hind limb suspension [8]. Accordingly, there was a possibility that ULLS would slow response speed of the fast component.…”
Section: Response Speed Of the Fast Componentmentioning
confidence: 98%
See 1 more Smart Citation
“…Kitahara et al 24 did not find differences in arm perimeter or in the magnetic resonance images after 21 days of elbow immobilization in healthy subjects. McDougall et al 25 , however, found a 5% reduction in arm perimeter after five weeks of elbow immobilization in healthy subjects.…”
Section: Discussionmentioning
confidence: 87%
“…Although limited and indirect, it is used in the clinical set-up to determine inter-limb differences and has been used to estimate muscle mass 1,2,24 . The arm perimeters were similar between the pre-and post-immobilization evaluation, suggesting that the perimeter is not a good tool to estimate muscle mass, that the reduction in muscle mass was offset by an increase in subcutaneous fat tissue, or that muscle mass does not change after fourteen days of immobilization in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%